A 2003 Social Accounting Matrix for Kenya - Kiringai, Jane; Thurlow, James; Wanjala, Bernadette (International Food Policy Research Institute, 2006)
The 2003 Kenya Social Accounting Matrix (SAM) is a consistent data framework that captures the information contained in the national income and product accounts and the input-output table, as well as the monetary flows between households, government and other institutions. The Kenya SAM also used surveys to estimate the production technology underlying different sectors of the economy. By combining this information with the country's household income and expenditure survey, the SAM provides a comprehensive picture of the structure of the Kenyan real economy in 2003.